2013
DOI: 10.1007/s10461-013-0626-6
|View full text |Cite
|
Sign up to set email alerts
|

Investing in Communities: Evaluating the Added Value of Community Mobilization on HIV Prevention Outcomes Among FSWs in India

Abstract: Community mobilization often requires greater time and resource investments than typical interventions, yet few evaluations exist to justify these investments. We evaluated the added benefit of community mobilization on HIV prevention outcomes among female sex workers (FSWs) using a composite measure of volunteer participation in program committees by FSWs. After adjusting for treatment propensity, we used multilevel structural equation modeling (MSEM) to test our program theory. We hypothesized that stronger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 34 publications
2
39
0
Order By: Relevance
“…The published work from India on successful strategies among the FSW population included one or all of the following: increased coverage, peer-led service delivery and education, condom social marketing and distribution, training in the skills necessary for their negotiation to condom use and utilization of services, 32 34 community engagement, and networking at all levels. 35 , 36 In India, HIV prevention interventions have placed FSWs at the center of the programs and, in fact, have used them as peer educators at a micro level to the community boards at the macro level to scale up the HIV prevention program. 37 For instance, the interventions in selected states of India have shown that the FSW community were represented in various forums of the HIV prevention projects, including crisis response, program planning, and district/state committees on HIV prevention programs.…”
Section: Way Forwardmentioning
confidence: 99%
“…The published work from India on successful strategies among the FSW population included one or all of the following: increased coverage, peer-led service delivery and education, condom social marketing and distribution, training in the skills necessary for their negotiation to condom use and utilization of services, 32 34 community engagement, and networking at all levels. 35 , 36 In India, HIV prevention interventions have placed FSWs at the center of the programs and, in fact, have used them as peer educators at a micro level to the community boards at the macro level to scale up the HIV prevention program. 37 For instance, the interventions in selected states of India have shown that the FSW community were represented in various forums of the HIV prevention projects, including crisis response, program planning, and district/state committees on HIV prevention programs.…”
Section: Way Forwardmentioning
confidence: 99%
“…However, strategies to increase CE have not been well described, and likely entail intervening at multiple levels of the socio-ecological model (SEM)including interpersonal, intrapersonal, organizational, community, and policy [12]. There is a lack of research on how to operationalize CE concepts in interventions and use CE as a focus of change and a unit of measure in multilevel community interventions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Reports of motherhood among FSWs in sub-Saharan Africa (SSA) are common, with most studies suggesting greater than 65% of FSWs have at least 1 biological child. [1][2][3][4][5] Reports of motherhood among FSWs in sub-Saharan Africa (SSA) are common, with most studies suggesting greater than 65% of FSWs have at least 1 biological child.…”
Section: Introductionmentioning
confidence: 99%
“…In SSA, antenatal care (ANC) has been cited as an entry point for women into health services, particularly regarding access to HIV testing, counseling and care (HCT), participation in prevention of mother-to-child HIV transmission programming (PMTCT) for HIV-infected women, and perinatal and postnatal maternal and infant health services. 2,5,[25][26][27][28] However, whether pregnancy or motherhood may propel FSWs to move beyond barriers that have been shown to reduce their participation in health services is largely unknown. 3,8,24 What has been consistently reported is the heightened burden of HIV among FSWs, with data indicating that FSWs are more than 12 times as likely to be living with HIV than other women of reproductive age (15-49 years) across SSA.…”
Section: Introductionmentioning
confidence: 99%